Моделі підготовки майбутніх учителів у європейських країнах - Кучай Тетяна; Орос Ільдіко; Kuchai Tatiana; Oros Ildiko; Kucsáj Tetjána; Orosz Ildikó (МНУ імені В. О. Сухомлинського, 2017)
Резюме. У статті розкривається моделі підготовки майбутніх учителів у європейських країнах. Виявлено особливості організації процесу підготовки вчителів у країнах, таких як: Велика Британія, Франція, Німеччина, Данія, Австрія, Бельгія, Польща. Висвітлюється потреба тісної співпраці університетів у сфері наукових досліджень та обміну професійним педагогічним досвідом для функціонування єдиного європейського освітнього простору.

Abstract. The article reveals models for the training of future teachers in European countries. The peculiarities of organizing the teacher training process in countries such as: Great Britain, France, Germany, Denmark, Austria, Belgium, Poland are revealed. The need for close cooperation of universities in the field of scientific research and the exchange of professional pedagogical experience for the functioning of a single European educational space is highlighted. Numerous exchange programs for scientific and pedagogical workers, joint inter-university research projects, the involvement of the industrial sector in the process of scientific activity of future specialists – all of this contributes to the emergence of higher academic education in the EU countries to a qualitatively new level – the level of internationalization, which involves the development of professional ties universities on the basis of international pedagogical and research cooperation.

Резюме. В статье раскрывается модели подготовки будущих учителей в европейских странах. Выявлены особенности организации процесса подготовки учителей в странах, таких как: Великобритания, Франция, Германия, Дания, Австрия, Бельгия, Польша. Освещается потребность тесного сотрудничества университетов в сфере научных исследований и обмена профессиональным педагогическим опытом для функционирования единого европейского образовательного пространства.
Future teacher training models in the Eeuropean countries
http://mdu.edu.ua/wp-content/uploads/Nauk_visnik-4-59-2017.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005892
Keywords: підготовка вчителів; різні країни; освіта; Європа